The Effect Of Digital Transformation Strategy On Financial Performance Of Pt Telkom Indonesia 2020–2024 - Sihombing, Josua Adrio; Simatupang, Simeon Adrian; Simamora, Vailimlim; Sihaloho, Fahmi Ashari (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the effect of digital transformation strategies on the financial performance of PT Telkom Indonesia during the period 2020–2024. Digital transformation in this study focuses on three main indicators, namely digital capital expenditure, the number of new digital services launched, and business unit restructuring as part of organizational adjustments to technological developments. The company's financial performance is measured using two main indicators, namely net profit and Earnings Before Interest, Taxes, Depreciation, and Amortization (EBITDA), which represent the company's profitability and operational efficiency. This study uses a quantitative approach with multiple linear regression analysis to examine the relationship between digital transformation variables and financial performance. The results show that digital capital expenditure and digital service innovation have a positive and significant effect on EBITDA, indicating that digital investment and new service development can improve the company's operational efficiency in the medium term. Conversely, business unit restructuring shows a negative effect on EBITDA in the short term, which is thought to be due to organizational adjustment and operational transition costs. However, the three digital transformation variables did not show a significant effect on the company's net profit during the observation period. These findings confirm that the impact of digital transformation strategies is more quickly reflected in increased operational efficiency than in the company's final profitability. This research contributes to the development of managerial economics theory, particularly in the context of digital investment decision-making, and provides practical implications for company management and policymakers in evaluating the effectiveness of digitalization strategies